2021
DOI: 10.1177/00219096211034526
|View full text |Cite
|
Sign up to set email alerts
|

Populism From Below and Social Movements: A Case of Zimbabwe’s #ThisFlag Movement

Abstract: This study examines a new wave of populisms arising in the digital era using Pastor Evan Mawarire’s #ThisFlag movement: What are they, and how do they express themselves? How does the hegemony react to them? Non-mainstream, digitally born movements, especially in dictatorships, are dismissed by the political elite as ill-mannered disruptors whose political interventions are detrimental. To analyse the cleric’s populism and its meaning to the Zimbabwean body politic, we use three specific themes: (a) personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Study also has shown that online platforms help in conjuring up collective and cross-sectarian narratives that challenge the hegemonic political narratives and heighten the countries identity (Badmus et al, 2019). Others contend that social media inspires populism from below (Theophilus and Mpofu, 2021) and that such movements can shed light on long-standing struggle and inequalities, can increase opportunities for the disadvantage groups and can open the societies to liberalised political economy (Ashine and Berhanu, 2021; Buranajaroenkij et al, 2018; Zaman, 2018). These with few exceptions all eulogise the access and organising abilities that social media platforms afford their users, particularly the chance they give to disadvantaged communities.…”
Section: Introductionmentioning
confidence: 99%
“…Study also has shown that online platforms help in conjuring up collective and cross-sectarian narratives that challenge the hegemonic political narratives and heighten the countries identity (Badmus et al, 2019). Others contend that social media inspires populism from below (Theophilus and Mpofu, 2021) and that such movements can shed light on long-standing struggle and inequalities, can increase opportunities for the disadvantage groups and can open the societies to liberalised political economy (Ashine and Berhanu, 2021; Buranajaroenkij et al, 2018; Zaman, 2018). These with few exceptions all eulogise the access and organising abilities that social media platforms afford their users, particularly the chance they give to disadvantaged communities.…”
Section: Introductionmentioning
confidence: 99%